Use of livestock resources for food security in the light of climate change - CGIAR Research Program on Livestock (2017)
Policy brief examining the role of genetic diversity in adapting African livestock production to climate change and making it more sustainable. Some breeds are more resilient to harsh climate than others; to the extent that breeding can improve productivity, it could reduce livestock’s environmental impact. The brief is based on an international seminar “Livestock Resources for Food Security in the Light of Climate Change”, held in March 2016 at SLU. https://www.siani.se/publication/use-livestock-resources-food-security-light-climate-change/